A história da didática no Instituto de Educação Leônidas do Amaral Vieira - Santa Cruz do Rio Pardo (1953-1975) - Reis, Viviane Cássia Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this text, I present Master's search results in Education, developed under the research program The history of Didactics in teacher training institutions in Brazil - 1827- 2011, which is due to the research project with the same name, that started in 2012, which is mainly aimed to identify, collect, select, organize, analyze and interpret aspects of didactics, as a discipline and field of knowledge in teacher training institutions in Brazil between 1827 and 2011. In this sense, this research has as main objective to locate, identify, collect, select, organize, analyze, interpret aspects of the body of knowledge, considered to be properly of didactics at the Institute of Education do Amaral Vieira Leonidas, in the city of Santa Cruz do Rio Pardo-SP, between 1953 and 1975, period of operation of this Institute and at the same time, during the which coexisted in the region of the city of Santa Cruz do Rio Pardo-SP two models of courses focused on training primary school teachers; one considered mid-level, the normal schools; and another, of higher level, the course of Pedagogy. Still, I hope to contribute to the production of a Didactics history in Brazil, that assist in finding solutions to the problems of education in the present, and the development of related research. This formulation originates from the belief that, studies that seek to systematize, analyze, and interpret aspects of the history of the disciplines in various teacher training institutions in Brazil contribute to the history of these disciplines in Brazil, for a history of teacher education in Brazil and, ultimately, contribute to the history of education in Brazil. Thus, this research is justified, centered in the history of body of knowledge considered to be properly of discipline Didactics, at the now defunct Institute of Education Leonidas do Amaral Vieira, in which, like the other Institutes of Education, created in cities state of São Paulo, the training...

Neste texto, apresentam-se resultados de pesquisa de Mestrado em Educação, desenvolvida, no âmbito do programa de pesquisa A história da didática em instituições de formação de professores no Brasil - 1827-2011, do qual é decorrente o projeto de pesquisa com a mesma denominação, iniciado em 2012, o qual tem como objetivo central identificar, reunir, selecionar, sistematizar, analisar e interpretar aspectos da Didática, como disciplina e campo de conhecimento em instituições de formação de professores no Brasil, entre 1827 e 2011. Nesse sentido, tal pesquisa, tem como objetivo geral localizar, identificar, reunir, selecionar, sistematizar, analisar, interpretar aspectos do corpo de saberes, considerado como sendo propriamente da disciplina de Didática no Instituto de Educação Leônidas do Amaral Vieira, da cidade de Santa Cruz do Rio Pardo-SP, entre os anos de 1953 e 1975, período de funcionamento desse Instituto e, ao mesmo tempo, período em que coexistiram na região da cidade de Santa Cruz do Rio Pardo-SP dois modelos de cursos centrados na formação de professores primários; um considerado de nível médio, as escolas normais; outro, de nível superior, o curso de Pedagogia. Ainda, espero contribuir para a produção de uma história da Didática no Brasil que auxilie na busca de soluções para os problemas desse ensino, no presente, e para o desenvolvimento de pesquisas correlatas. Tal formulação se originou da crença de que, pesquisas que buscam sistematizar, analisar, e interpretar aspectos da história das disciplinas nas diversas instituições de formação de professores no Brasil contribuem para uma história dessas disciplinas no Brasil, para uma história da formação de professores no Brasil e, no limite, contribuem para uma história da educação no Brasil. Assim, se justifica esta pesquisa, centrada na história do corpo de saberes considerado como sendo propriamente da disciplina de...
Keywords: Educação - Santa Cruz do Rio Pardo (SP) - 1953- 1975; Educação - Historia; Didática; Professores - Formação; Education